COMPARATIVE EVALUATION OF PARAMETERS SINGLE LAPAROSCOPIC ACCESS AT ANATOMICAL RESEARCH AND SPIRAL COMPUTED TOMOGRAPHY - Рустам Габдылоханович Ахметзянов; Юрий Борисович Развозжаев; Андрей Игоревич Баранов; Алексей Алексеевич Фаев; Иван Юрьевич Данильченко; Андрей Владимирович Алонцев (Медицина в Кузбассе, 2019)
Objective. Parameters of a single laparoscopic access (LA) to the base of the appendix, the neck of the gallbladder and the duodenal bulb (DB).